Promoting Healthy Eating Habits: The Role of Community-Based Research in Nutrition - Serengil Ozcelik, Melike (Journal of Neonatal Surgery, 2025)
Obesity, cardiovascular disease, and type 2 diabetes are primarily caused by sedentarism, poor physical exercise, and unhealthy eating habits. Adopting healthy eating habits is a priority for authorities and nutrition researchers, aiming to guide societies towards a healthy life. In public health, community-based research (CBR), also commonly named as community-based participatory research (CBPR) (CBR and CBPR are substitutes for each other in this paper) emphasizes social, related to structure, and physical environmental injustices by actively including researchers, community members, and representatives of organizations in all phases of the study. Partners provide their knowledge to deepen comprehension of an issue and to put that understanding into practice for the benefit of the community overall. In recent years, community health research and practice have increasingly embraced partnership models, which place an emphasis on community impact and involvement in community-beneficial research endeavors. Though the majority of researchers agree that communities must be involved in community-based research, there isn't a single, generally acknowledged approach or set of guidelines for community engagement. The purpose of this paper is to highlight the role and power of community-based research in promoting healthy eating habits in communities.